2023
DOI: 10.3390/molecules28041925
|View full text |Cite
|
Sign up to set email alerts
|

Novel 2-Thiouracil-5-Sulfonamide Derivatives: Design, Synthesis, Molecular Docking, and Biological Evaluation as Antioxidants with 15-LOX Inhibition

Abstract: New antioxidant agents are urgently required to combat oxidative stress, which is linked to the emergence of serious diseases. In an effort to discover potent antioxidant agents, a novel series of 2-thiouracil-5-sulfonamides (4–9) were designed and synthesized. In line with this approach, our target new compounds were prepared from methyl ketone derivative 3, which was used as a blocking unit for further synthesis of a novel series of chalcone derivatives 4a–d, thiosemicarbazone derivatives 5a–d, pyridine deri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0
3

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 48 publications
0
4
0
3
Order By: Relevance
“…Found, %: С 55. 19 (17), 95 (20), 70 (18), 69 (12), 56 (25). Found, %: С 54.54; Н 4.59; N 10.12; S 7.…”
Section: Experimental Partmentioning
confidence: 98%
See 1 more Smart Citation
“…Found, %: С 55. 19 (17), 95 (20), 70 (18), 69 (12), 56 (25). Found, %: С 54.54; Н 4.59; N 10.12; S 7.…”
Section: Experimental Partmentioning
confidence: 98%
“…However, they include compounds with different biological activities: hypoglycaemic [1,2], antitumour [3], antiviral [4][5][6][7][8][9], antiepileptic [10], hypotensive [11], antiprotozoal [12], antifungal [13], anticancer [14][15][16], anti-inflammatory [17], diuretic [18], etc. [19][20][21]. Also, sulfonylamides are a convenient and efficient source of nitrogen and are used in the construction of C-N bonds [22].…”
Section: Introductionmentioning
confidence: 99%
“…Традиционно сульфониламиды рассматриваются как антибактериальные агенты, но среди них можно найти соединения с различной биологической активностью, например гипогликемической [1,2], противоопухолевой [3], противовирусной [4][5][6][7][8][9], противоэпилептической [10], гипотензивной [11], антипротозоальной [12], противогрибковой [13], противораковой [14][15][16], противовоспалительной [17], диуретической [18] и др. [19][20][21]. Кроме того, сульфониламиды являются удобным и эффективным источником азота и используются при построении связей С-N [22], а аддукт сульфониламида и витамина С улучшает оптические свойства поливинилового спирта, что делает возможным его использование в производстве оптических устройств [23].…”
Section: Introductionunclassified
“…Recently, Ahmed et al reported new 2-thiouracil-5-sulfonamide derivatives and their biological properties [39].…”
Section: Introductionmentioning
confidence: 99%